Consulting report - Bigmond mexican market entry business plan - Marin Anicama, Mónica Giuliana (2018)
Bigmond is a Peruvian company dedicated to the search of top executives offering a superior value proposition in the market. Given the great acceptance in Peru, the firm is keen to expand its commercial activities to Mexico to become a multinational company. The objective of the project is to develop a viable business plan for Bigmond's entry into the Mexican Executive search market. An external market analysis was carried out to identify opportunities and threats that could influence the success of the project. In addition, an industry analysis to assess Porter’s Five Forces was carried out. After identifying the key factors, a qualitative and quantitative study of the Mexican market was conducted to define the target market of the project in which Bigmond should focus. The historical development of Mexico's industries, the growth forecast, the demand for talent by sector, the provision for outsourcing services in companies, the concentration of potential companies at the regional level and the main market trends were taken into consideration for the assessment. Results showed that the target market should focus on the central region of Mexico and on the development of the technology industry in each of these four main economic sectors: Marketing and Communications, Manufacturing, and Financial Services and Construction. Within a next step opening a branch in Mexico City has been identified as the most suitable entry strategy for Bigmond. Then, the implementation plan included the marketing mix, which showed that one of the key success factors will be the development of brand equity. Finally, the financial analysis indicated a resulting economic TIR of 102.5% and a NPV of US $ 309,000. In addition, a sensitivity analysis assessed the expected market share. Findings of the nine scenarios showed an expected minimum IRR above 15% and a NPV greater than zero. This leads to the conclusion that establishing a commercial activity in the Mexican market is a feasible option with a promising outlook for Bigmond.